1999
DOI: 10.2116/analsci.15.1185
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Ion-Pair Extraction of Potassium Chloride from Aqueous Phase into Nitrobenzene Containing Dicyclohexyl-18-crown-6 as Cation Binder and Diphenylthiourea as Anion Binder

Abstract: Ion-pair recognition of cationic and anionic guest species by bifunctional receptors is a current topic in molecular recognition chemistry. [1][2][3][4][5] Recently Beer et al. have designed novel rhenium(I) bipyridyl amide crown ether receptors and shown that these receptors complexed to form K + Cl -ion pairs in which complexation of crown ether moiety with K + cooperated in the binding of Cl -in organic solution. 6 Reinhoudt et al. have also shown that calix[4]arenes bearing urea moieties behave as bifuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These nearnormal Hofmeister systems thus lie in the lower left box in the selectivity model shown in Figure 2. Examples in liquid/ liquid extraction include diphenylurea [45] and m-diphenyldisulfonamides, [20,46] though peak selectivity for iodide has been claimed for monothiouronium receptors.…”
Section: Multipoint Recognitionmentioning
confidence: 99%
“…These nearnormal Hofmeister systems thus lie in the lower left box in the selectivity model shown in Figure 2. Examples in liquid/ liquid extraction include diphenylurea [45] and m-diphenyldisulfonamides, [20,46] though peak selectivity for iodide has been claimed for monothiouronium receptors.…”
Section: Multipoint Recognitionmentioning
confidence: 99%
“…Ion‐pair recognition of cationic and anionic guest species by bifunctional receptors is a current topic in molecular recognition chemistry 6. In ion‐pair extractive separation of metal cations using a complexation reagent and a counter anion is one of the most important factors to realize their mutual separation.…”
Section: Introductionmentioning
confidence: 99%
“…This provides strong evidence that the extraction of thiourea with the TOMA ion-pairs studied takes place via the formation of a heteroconjugate anion. Other reports support this conclusion since they have shown that anions can interact with thiourea or its derivatives through hydrogen bonding [9][10][11][12][13].…”
Section: Anionmentioning
confidence: 86%
“…Interactions in organic solvents between uncharged organic molecules, acting as hydrogen bond donors, and small inorganic anions have been used successfully in analytical separation and sensing [7][8][9][10][11][12][13]. The formation of the corresponding heteroconjugate anions results in the stabilization of the small inorganic anions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation